Evaluation of Mangrove Ecosystem Rehabilitation Program in Limbatihu Village - Idrak Saleh; Abd Hafidz Olii; Hasim Hasim (The NIKe Journal, 2019)
This research was conducted in the village of Limbatihu which runs from January to March 2015 with the aim of this study was to determine the success of the program of rehabilitation of mangrove ecosystems in the District Limbatihu village district was Paguyaman Pantai.The method used is a survey method, interviews, and collecting secondary and primary data to support research conducted by the researchers.The data analysis used descriptive analysis to look at the program of rehabilitation of mangrove ecosystems.The results of this study address that the program of rehabilitation of mangrove ecosystems in the village Limbatihu known to succeed because with the support of local communities and government local village, the successful rehabilitation of the mangrove ecosystem can be seen the value of the participation of the government and local communities to support the implementation of rehabilitation activities carried out by Japesda. Keywords: Rehabilitation; mangrove; ecosystem; rural.